(untitled) (Vietnam Journal of Community Medicine, 2026)
Background: Femoral shaft fractures are severe injuries associated with significant blood loss, shock, and potential mortality, accounting for approximately 5–10% of all fractures. Locked intramedullary nailing is considered the gold standard for treatment due to its ability to provide stable fixation and promote rapid bone union. At Nghe An Friendship General Hospital, this technique has been implemented since 2016; however, a comprehensive evaluation has not yet been conducted. Therefore, this study was performed to analyze the characteristics and treatment outcomes of this method. Objective: To evaluate the outcomes of surgical treatment of closed femoral shaft fractures using interlocking intramedullary nailing with open reduction without fluoroscopic guidance in trauma patients treated from January 2024 to July 2025 at Nghe An Friendship General Hospital. Subjects and Methods: A retrospective and prospective descriptive study was conducted from January 2024 to July 2025. Clinical and paraclinical data, fracture patterns, surgical techniques, and treatment outcomes were collected and analyzed. Outcomes were assessed based on wound healing, quality of fixation, bone union, functional recovery, and complications. Results: The mean age was 33.64 ± 17.09 years, with patients aged ≤40 years accounting for 67.86%. Males represented 76.79% of the study population. Traffic accidents were the most common cause (89.28%). Most fractures occurred in the middle third of the femoral shaft (66.07%), with transverse fractures accounting for 44.64% and AO classification type A3 representing 48.21%. The distribution between left and right femurs was equal. Primary wound healing was achieved in 98.21% of cases. Fixation results were rated as very good in 76.79% and good in 23.21%. Good and very good bone union was observed in 85.72% of patients. Functional recovery was very good in 85.71% and good in 8.93%. The overall good and very good outcome rate was 89.79%. Conclusion: Open reduction with locked intramedullary nailing is an effective method for treating closed femoral shaft fractures, achieving a bone union rate of 85.72% and good to very good functional recovery in 94.64% of patients in this study.